POLITIK PENDIDIKAN ISLAM DI INDONESIA: DINAMIKA KEBIJAKAN NEGARA TERHADAP MADRASAH DAN PESANTREN - Afriantoni; Rahmani Uswatun Khasanah; Cindi Amanda Nabila Sari; Ayattullah Omar; M. Zaky Maulana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the dynamics of Islamic education politics in Indonesia, focusing on state policies toward madrasahs and pesantrens. The novelty of this research lies in its comparative analysis of state policy patterns toward these two Islamic educational institutions across different political periods in Indonesia. This study employs a qualitative approach using library research enriched by netnography. Data were collected from books, scholarly journals, policy documents, and relevant digital sources and analyzed descriptively. The findings show that Islamic education policies have evolved from marginalization and integration to standardization and greater recognition during the Reform era. Madrasahs have been directed toward standardization and integration into the national education system, while pesantrens have retained broader institutional autonomy. The study concludes that Islamic education politics is a process of negotiation between the state and Muslim society that requires inclusive and adaptive policies to improve educational quality while preserving Islamic identity